The Impact of a Structured Physical Exercise Program on Physical Function and Quality of Life among Patients with Chronic Kidney Disease Undergoing Hemodialysis - Friska Ernita Sitorus; Alprindo Sembiring Meliala; Hariati Hariati; Jekson Martiar Siahaan; Rostiodertina Girsang; Bahtera Bindavid Purba; Putri Ayu Yessy Ariecha; Nurul Aini Siagian; Peny Ariani; Tetty Junita Purba; Elmina Tampubolon (KHD-Production, 2026)
Chronic kidney disease is a progressive condition characterized by a permanent decline in kidney function and requires renal replacement therapy, one of which is hemodialysis. Patients with chronic kidney disease undergoing hemodialysis often experience decreased physical function and quality of life due to activity limitations, fatigue, and psychological impacts. One non-pharmacological therapy that can be applied to address these problems is a physical exercise program. This study aims to determine the effect of a physical exercise program on physical function and quality of life among patients with chronic kidney disease undergoing hemodialysis at Sembiring General Hospital Deli Tua in 2026. This study used a quasi-experimental design using a one-group pretest–posttest approach. Sampling was conducted using a purposive sampling technique, resulting in a total sample of 54 respondents. Data analysis was performed using the Wilcoxon test with a significance level of α=0.05. The results showed that the mean score of physical function before the intervention was 54.56 and increased to 57.50 after the intervention. Similarly, the mean score of quality of life increased from 56.83 before the intervention to 58.93 after the intervention. The Wilcoxon test analysis revealed a p-value of 0.000<α=0.05 for both physical function and quality of life. The conclusion shows that the physical exercise program had a significant effect on improving physical function and quality of life among patients with chronic kidney disease undergoing hemodialysis at Sembiring General Hospital Deli Tua in 2026. It is recommended that physical exercise program can be implemented for patients with chronic kidney disease to enhance their physical function and quality of life.